Integrative role of the histaminergic system in feeding and taste perception - Ishizuka, Tomoko; Yamatodani, Atsushi (Frontiers in Systems Neuroscience, 2012)
Feeding behavior is regulated by a complex interplay of many endogenous substances, such as peptides and neurotransmitters in the central nervous system. Histamine is a neurotransmitter which expresses an anorectic effect on food intake via histamine H1 receptors. The histaminergic system exists downstream of leptin, a satiety factor secreted from white adipose tissue. Because direct stimulation of the histaminergic system by histamine H3-inverse agonists or antagonists can normalize the obese phenotype in which animal models with exogenous leptin resistance, which resembles human obesity, the potential roles of histamine H3 receptors as a therapeutic target now draw attention. Histaminergic activity is enhanced during feeding, and an oral somatic sensation is thought to affect histaminergic activity while blood glucose levels do not. In addition, gustatory information can modulate histaminergic activity by two mechanisms: by physiological excitation of the chorda tympani nerve, one of the taste nerves, and by emotions elicited by taste perception, i.e. taste palatability. Particularly, aversive and hazardous taste stimuli tonically facilitate histaminergic activity, suggesting that the histaminergic system is involved in the response to harmful stimuli. Together with recent findings, it is postulated that the histaminergic system responds to both mechanical and chemical sensory input from the oral cavity during feeding and is exerted as a part of the danger response system.